PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SD PADA MATERI JENIS-JENIS PEKERJAAN TEMA 4 KELAS 4 - Famela Carollines, Agatha; Tamala Putri, Chika; Elvadola, Connyta (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2019)
The purpose of this research is to develop multimedia products as alternative media in learning in elementary schools. This research is a research and development or Research and Development (R&D). Borg and Gall. The result of this research is audio visual learning for class 4 theme 4 material type of work. The conclusion of this research is that education will continue to develop with advances in science and technology in the global world. Audio visual or multimedia that is developed is a combination of sound, music, images, text (writing), and animation using applications. The suggestion from this research is that the products produced must go through validation and trial before they are used or applied to students and teachers must be creative in innovating and can use other applications to develop multimedia so that they are not left behind.